Government Regulations and Gender Justice: Feminist Criticism and Maqāṣid al-Sharī‘ah on Polygamy Permits - Kartika Putri, Aulia; Qodir, Zuly; Suswanta, Suswanta (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2026)
The government supports discrimination against feminism based on Jakarta Governor Regulation No. 2 of 2025, which regulates the procedure for granting polygamy permits to civil servants (PNS), has caused controversy because it is considered unfair to women. This study aims to critically analyze discrimination against women in regulations through a critical feminist and gender justice ethics approach. The results show that procedures such as the first wife's consent are symbolic and do not reflect a balanced power relationship, while the religious justification used ignores the principle of justice in maqashid al-shariah. It is concluded that the Governor Regulation risks perpetuating male dominance in the state structure and weakening the position of women as legal subjects. This study contributes to public policy and gender studies by placing the governor's regulation as empirical evidence rather than the main analytical source, showing that gender inequality in bureaucratic policy is rooted in structural and ideological governance frameworks. These findings offer an analytical contribution that can be applied to assess gender justice in state regulations beyond the specific case analyzed. Therefore, this study recommends that such policies be evaluated through a more participatory and gender-justice-based approach, and encourages the formulation of public regulations that prioritize the protection and equality of women's rights in the bureaucracy.